MO1005ADPEDKD: A GLOBAL ONLINE PLATFORM TO EXPLORE THE CHILDHOOD PHENOTYPE OF AUTOSOMAL DOMINANT POLYCYSTIC KIDNEY DISEASE*. (29th May 2021) - Dachy, Angélique; De Rechter, Stéphanie; Guay-Woodford, Lisa; Mallett, Andrew John; Harris, Tess; Bockenhauer, Detlef; Schaefer, Franz; Liebau, Max; Mekahli, Djalila
Abstract: Background and Aims: Autosomal Dominant Polycystic Kidney Disease (ADPKD) is the 4th common cause of renal replacement therapy worldwide. As the disorder has been historically considered an adult-onset disease, there is a lack of longitudinal data from large pediatric cohorts. However, evidence is growing that first manifestations of ADPKD may be detected in childhood and children represent a specific target population for future treatment, allowing a better chance of preserving long term kidney function. To better define the pediatric spectrum of the disease, a global multicenter observational study on childhood-diagnosed ADPKD was launched in 2017. Method: The ADPedKD registry is a worldwide web-based database, including both retrospective and prospective longitudinal data from young ADPKD patients (≤ 19 years). Australia, North-America and the United Kingdom joined the initiative with their source databases, namely the KidGen Collaborative (KidGen), NIH-funded Hepato-Renal Fibrocystic Disease (HRFD) and National Registry of Rare Kidney Diseases (RaDaR). Under informed consent, de-identified patient data, including genetics, radiological and laboratory findings, treatments and follow-up were enrolled in the database accessible via https://www.ADPedKd.org/ . Results: 1019 ADPKD children (from 89 centers and 33 countries) are enrolled in the registry of which 167 patients from RaDaR, 17 from KidGen, 11 from HRFD and 824 from ADPedKD (401 male/ 423 female) with a mean (± SD) age at diagnosis of 6.3 ± 5.2 years. 81 children (9.8%) were diagnosed prenatally at a mean gestational age of 26.8 ± 7.8 weeks. Reasons for initial visit were: family screening in 325 (39.4%), postnatal incidental finding in 223 (27.0%), presenting features (such as hematuria, hypertension, urinary tract infections and flank or back pain) in 150 (18.2%) or unknown/not available in 126 (15.3%). Genetic testing was performed in 42.8% of the population, with the following results: PKD1 mutation (85.4%), PKD2 mutation (11.7%) and others (6.0%). Conclusion: The ADPedKD registry is a unique source of clinical observational data that will provide deep phenotyping of children with ADPKD and will allow to define unified diagnostic, treatment and follow-up recommendations.